2019
DOI: 10.1128/jvi.01432-18
|View full text |Cite
|
Sign up to set email alerts
|

A Single Adaptive Mutation in Sodium Taurocholate Cotransporting Polypeptide Induced by Hepadnaviruses Determines Virus Species Specificity

Abstract: Hepatitis B virus (HBV) and its hepadnavirus relatives infect a wide range of vertebrates, from fish to human. Hepadnaviruses and their hosts have a long history of acquiring adaptive mutations. However, there are no reports providing direct molecular evidence for such a coevolutionary “arms race” between hepadnaviruses and their hosts. Here, we present evidence suggesting that the adaptive evolution of the sodium taurocholate cotransporting polypeptide (NTCP), an HBV receptor, has been influenced by virus inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…The HDV supernatant was concentrated (x50) using an Amicon centrifugal filter (MWCO: 100 kDa, Merck, Germany) dHepaRG cells were infected with HDV at a MOI of 25 genome equivalents per cell in the presence of 5% polyethylene glycol (PEG) 8000 for 24 h. The cells were washed three times with medium to remove viral inoculum and cultured for an additional 6 days. HDV infection was evaluated by detecting HDAg by immunofluorescence assay and by quantifying HDV RNA by qRT-PCR as previously described 76 .…”
Section: Methodsmentioning
confidence: 99%
“…The HDV supernatant was concentrated (x50) using an Amicon centrifugal filter (MWCO: 100 kDa, Merck, Germany) dHepaRG cells were infected with HDV at a MOI of 25 genome equivalents per cell in the presence of 5% polyethylene glycol (PEG) 8000 for 24 h. The cells were washed three times with medium to remove viral inoculum and cultured for an additional 6 days. HDV infection was evaluated by detecting HDAg by immunofluorescence assay and by quantifying HDV RNA by qRT-PCR as previously described 76 .…”
Section: Methodsmentioning
confidence: 99%
“…HBV has been evolving together with Homo sapiens over millennia and many studies have reported the evolutionary “arms race” between the HBV and the host immune system (Kramvis et al, 2018; Lumley et al, 2018). Recently, two studies reported that HBV-related hepadnaviruses drive the evolutionary history of their mammalian host receptor and induce signatures of adaptive selection in the cellular receptor NTCP (Jacquet et al, 2018; Takeuchi et al, 2018). Host genes also influence the evolution of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hNTCP expression in cynomolgus macaque, rhesus macaque, and pig hepatocytes enables productive HBV infection, indicating that the barriers experienced in mice are not an issue in macaques [ 29 ]. Notably, amino acid residue 158 in hNTCP determines species specificity towards HBV infection in Old World Monkeys (OWM); substitution of this residue to that of cynomolgus macaque NTCP impedes HBV infection [ 42 ].…”
Section: Hbv Host Tropismmentioning
confidence: 99%